Distance learning course for scientific articles writting. - Míriam Gutiérrez Escobar; Raúl López Fernández; Loreta Sánchez Ortiz; Rachel Yanes Seijo; Rosa María Rodríguez Arencibia; Ana María Molina Gómez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Scientific publications within Medical Sciences are an important factor for professionals to achieve services of excellence. However, the training to write this kind of articles is not enough. Objective: To design a theoretical and practical course of composition and style for scientific articles publications. Methods: Observational, descriptive, cross-sectional study including 50 professionals of the Medical School Branch. The main difficulties that they face to publish an article were determined and a distance learning course was designed on this basis, using the Moodle platform. Results: All the surveyed individuals referred that among the main causes limiting their ability to publish scientific articles are: little practical knowledge about the requirements to write scientific articles, not receiving any subject enhancing textual composition during their academic formation, and not attending to any post-graduate course aimed at improving academic writing for publication. A curse of 10 hours (theoretical part) and 30 hours (practical part) divide into five chapters including stylistic, methodological and compositional elements. Conclusions: This course helps improving the composition of scientific articles written by professional and their further publication in scientific journals.